The relationship between physical activity and mental toughness among Chinese university students: the chain-mediated role of self-esteem and social support - Zhou, Zhixing; Xiang, Jun (Frontiers in Psychology, 2025)
BackgroundAs Chinese university students increasingly face psychological challenges such as academic pressure and employment-related stress, mental toughness has gained attention as a crucial trait for coping with adversity. Physical activity has been considered a potential way to enhance mental toughness, yet its underlying mechanisms remain insufficiently understood.ObjectiveThis study aimed to examine the associations between physical activity and mental toughness among university students, and to explore the potential mediating roles of self-esteem and social support.MethodsThis study used the Physical Activity Scale, the Self-Esteem Scale, the Social Support Scale, and the Mental Toughness Scale with 1,184 university students in Guangdong Province as the research subjects. Data were analyzed sequentially using Pearson correlation analysis, structural equation modeling test and bias-corrected percentile bootstrap.Results(1) Physical activity was positively correlated with mental toughness (r = 0.216), and the direct path between physical activity and mental toughness was significant (β = 0.085, p < 0.01, CI [0.04, 0.13]); (2) physical activity was positively correlated with self-esteem (β = 0.173, p < 0.01, CI [0.11, 0.23]) and social support (β = 0.063, p < 0.05, CI [0.08, 0.11]); self-esteem was positively correlated with social support (β = 0.397, p < 0.01, CI [0.34, 0.45]) and mental toughness (β = 0.350, p < 0.01, CI [0.30, 0.40]); and social support was positively correlated with mental toughness (β = 0.304, p < 0.01, CI [0.25, 0.35]); and (3) self-esteem and social support played a significant mediating role between physical activity and mental toughness. The mediating effect consisted of 3 pathways: physical activity → self-esteem → mental toughness (mediating effect value of 0.061), physical activity → social support → mental toughness (mediating effect value of 0.019), and physical activity → self-esteem → social support → mental toughness (mediating effect value of 0.021).ConclusionThe findings suggest that physical activity is positively associated with mental toughness among university students, and this relationship is partially mediated by self-esteem and social support. Given the cross-sectional nature of the study, conclusions about causality cannot be drawn.